Consumer Value, Digital Content Marketing, and Housing Purchase Intention in Urban Residential Markets - Syifa Hanifa Salsabil; Windarko Windarko (UNIVED Press, 2026)
Urban housing markets are becoming increasingly competitive, requiring a deeper understanding of factors that shape housing purchase intention. This study examines the influence of functional, emotional, social, and experiential value on housing purchase intention and investigates the mediating role of digital content marketing. Data were collected from urban housing consumers in the Greater Jakarta area and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that emotional and social value significantly influence housing purchase intention, while functional and experiential value do not. Digital content marketing shows neither a direct effect nor a mediating role in the proposed relationships. These findings suggest that housing purchase intention is driven primarily by emotional and social evaluations rather than digital marketing influence, highlighting the importance of value-based decision-making in urban housing markets.